Shame and Guilt in EMS: A Qualitative Analysis of Culture and Attitudes in Prehospital Emergency Care. (19th May 2023) - Hoff, J. J.; Zimmerman, Armand; Tupetz, Anna; Van Vleet, Lee; Staton, Catherine; Joiner, Anjni
Abstract: Study Objectives: The shame reaction is a highly negative emotional reaction shown to have long-term deleterious effects on the mental health of clinicians. Prior studies have focused on in-hospital personnel, but very little is known about what drives shame reactions in emergency medical services (EMS), a field with very high rates of post-traumatic stress disorder, burnout, anxiety, and depression. The objective of this study was to describe emotions, processes, and resilience associated with self-identified adverse events in the work of prehospital clinicians. Methods: We conducted a qualitative study using a modified critical incident technique. Participants were recruited from two EMS agencies in North Carolina: one urban and one rural. They provided an open-ended, written reflection in which they were asked to self-identify particular events in their EMS careers that felt emotionally difficult. In-person or video in-depth interviews about these events were then conducted in a semi-structured fashion using an iterative interview guide. The codebook was developed through a mix of inductive and deductive analysis strategies and discussed within the research team and a content expert for validation. Interviews were transcribed and data were analyzed following a thematic content analysis approach for types of cases identified as emotionally difficult, common emotional responses and coping mechanisms, and the lingering effects of these experiences on study subjects. Results: Eight interviews were conducted with EMS personnel: five from an urban agency and three from a rural agency. Participants commonly identified complex medical cases as being emotionally difficult, which led to the most robust shame reactions. Shame reactions were more common when EMS clinicians committed self-perceived errors in patient care, whereas guilt reactions were more common when patient outcomes seemed "inevitable" despite any intervention. Common themes related to coping mechanisms included both personal mechanisms, which tended to be less successful compared to interpersonal mechanisms, particularly when emotions were shared with colleagues. This reflected a perceived culture change within EMS in which sharing emotions with colleagues was seen as a departure from the "old school" where emotions tended to be kept to oneself. Feelings of inadequacy, low self-worth, and being "not good enough" were frequently identified as lingering emotions after difficult cases that were hard to move on from, corresponding to longstanding shame in these clinicians. Recovery and resilience varied but tended to be positively associated with a culture in which sharing with colleagues was encouraged, along with personal introspection on root causes for the sentinel event. Conclusion: EMS clinicians often identify complex patient cases as those leading to emotions such as shame and guilt, with shame reactions being more common when a perceived error was committed. Coping mechanisms were varied, but individuals often relied on their coworkers in a sharing environment to adequately process their negative feelings, which was seen as a departure from past practices in EMS personnel. Our hope is that future studies will be able to use these findings to identify targets for intervention on negative mental health outcomes in EMS personnel.